KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KOMUNIKASI ORGANISASI PENGARUHNYA TERHADAP KOMITMEN ORGANISASI GURU - Zainuddin, Zainuddin; Badrudin, Badrudin; Haryanti, Erni (Universitas Nurul Jadid, 2020)
This study was conducted to reveal the principal's transformational leadership and organizational communication its effect on teacher organizational commitment. This study uses a quantitative approach with a survey method with a total sample of 28 teachers. The data collection technique used a questionnaire with a Likert scale. Data were analyzed using simple and multiple correlation and regression techniques. The results of this study indicate that the principal's transformational leadership and organizational communication have a joint effect on the variable of teacher organizational commitment by 92.2% which means very strong. So it can be concluded that the better the principal's transformational leadership and organizational communication, the better the teacher's organizational commitment.